Familiar, retórica, cortesana: disfraces de la carta en los tratados epistolares renacentistas - Martín Baños, Pedro (Cuadernos de Historia Moderna, 2006)
The purpose of this article is to explore the three main theoretical points of view about the letter (clearly differentiated, although not necessarily one against the other) that appear in Renaissance treatises. In a first type of manuals, the letter is seen like a familiar text, near the common language and equated to a carefree and spontaneous conversation between friends. In the opposed pole, the letter can be also understood like a rhetorical, skillful document, composed in agreement with the same norms that govern the composition of the oratio or oral speech. Besides these two ideas of the epistle, familiar and rhetoric, both born in neo-latin humanism, a new conception arises in the second half of 16th century, in the context of an abundant corpus of letter formularies and manuals for secretaries written in the vernacular tongues: the conception that considers the epistle like the expression of the courtly or courteous society and spirit.